Experimental study on concrete with rice husk ash under sulphuric ACID solutions - Ramya Swetha, R.; G.Venkata Ramana, Dr.; Anusha Hadassa, K. (International Journal of Engineering and Technology, 2018)
This investigation shows the results on aggressive sulphuric acid on the concrete combined with rice husk ash (RH) when partially replaced for ordinary Portland cement. The husk ash, which mainly contains aluminum ion, silica, iron and calcium oxides, is an industrial waste and poses disposal problems. In this study, the effect of various concentrations (1%, 3%, 5%) of sulphuric acid (H2SO4) on Concrete replaced with various percentages (0%,5%,10%,15% and 20% by weight of cement) of RH is evaluated in-terms of residual compressive strength. The loss of compressive strengths of concrete immersed in various H2SO4 solutions for 7 days 28 days and 60 days indicates that at upto 10% replacement increase in strength was observed after which strengths were decreasing. This increase in strength is attributed to pozzolanic activity of RH.Â Â